Preparation of fusarium oxysporum-inhibiting chito-oligosaccharide by chitin/chitosan-hydrolyzing enzyme from actinomycetes - Van Anh, Trinh Thi; Quynh Uyen, Nguyen; Ngoc Hong, Nguyen; Thi Lam, Dinh; Van Vinh, Hoang (Vietnam Journal of Biotechnology, 2021)
Chito-oligosaccharide (COS), one of remakable derivatives of chitosan, has almost chitosan’s biological function but better activities in antibacteria, antifungi and plant elicitor… Producing COS by biological enzymes shows many advantages in comparision with physical and chemical methods. In our study, COS was prepared using chitin/chitosan-hydrolyzing enzyme from actinomycetes. By analysis of 16S rDNA sequence, the enzyme producer VTCC 940003 belonged to Streptomyces macrosporeus. The strain’s ability to synthesize the enzyme having chitin/chitosan-hydrolyzing activity was first detected by agar plate method and then its activity equivalent to chitinase activity was determined using dinitrosalicylic acid (DNS). The enzyme activity in the strain culture was 24 ± 0.05 U/ml. The COS was prepared by using the enzyme from S. macrosporeus VTCC 940003 to hydrolyze chitosan. The degree of polymerization (DP) of the obtained COS was mainly DP3-DP5. At the concentration of 0,3‰ the COS inhibited 98% of spore germination of Fusarium oxysporum after 24 hours and this activity remained after 48 hours.